Semiconductive Covalent Organic Frameworks: Structural Design, Synthesis, and Application. Issue 2 (9th September 2020) - Wang, Shizhao; Xu, Xiaoyi; Yue, Yan; Yu, Kunshan; Shui, Qingjun; Huang, Ning; Chen, Hongzheng
Abstract : Semiconducting polymers with ordered structures and self‐segregated nanophases are highly desirable in the development of high‐performance photovoltaic devices. Based on the reticular chemistry, covalent organic frameworks (COFs) have emerged as an attractive material platform with crystalline structure and intrinsic porosity, which can be obtained through the combination of the predesigned topological diagrams and bottom‐up synthetic strategy. Significantly, various functional building blocks can be assembled into the skeletons of COFs at atomic precision, thus accurately regulating and controlling their semiconducting properties. Herein, an overview on recent advances of semiconducting COFs, sketching the programs from structural design to synthetic approach and functional exploration is given. Abstract : Due to the tightly stacking π‐aromatic units and periodically aligned lattices, covalent organic frameworks (COFs) have been widely explored as semiconducting materials. Combined with high crystallinity, rich porosity, and excellent semiconductivity, COFs have been widely applied in optoelectronics, electrocatalysis, and sensing.